A teacher’s perception on the use of online assessment for reading comprehension - Anggi Aulia Rahma; Intan Pradita (Concept : Community Concern for English Pedagogy and Teaching, 2020)
The purpose of this research is to investigate the data related to teacher’s perception on the use of online assessment for assessing reading comprehension in higher education. In this study, the researcher used Qualitative Approach, which is thematic analysis is the foundation method of qualitative research. To identify the teacher perception on the use online assessment to assess reading comprehension, researcher will used interview to collect the data. The participants in this study were intensive reading lecturers of English language education program in Yogyakarta. The results of this study indicate that reading comprehension assessment using the online platform as a tool can assist teachers in assessing student work. In addition, by not giving restrictions to students in working on the task of making answers to their assignments beyond the teacher's expectations. Keywords: Online Assessmen;, Reading Comprehension; Online Platform; Restriction